(untitled) (Global Journal of Management and Business Research, 2022)
There is no easy way to maintain employee loyalty to an organization in order to retain employees. There are several variations that contribute to employee loyalty in the hotel industry such as job development, compensation and rewards, job security and the workplace. Therefore, this study was conducted to study the relationship between these four variables and employee loyalty that could reduce the rate of change in the hotel industry. Based on previous research, there is an important relationship between these variables with employee loyalty. In the study, there is other evidence that can prove that staff loyalty is reliable in these four variables.